Tradisi Tarian Gubang dalam Prosesi Pra Pernikahan di Desa Mampok Perspektif ‘Urf - Muhamad Habib (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research examines the marriage tradition of the Indonesian people in Mampok village, Jemaja sub-district, namely the Gubang dance tradition in the pre-marriage procession. This tradition presents the Gubang dance in a series of pre-marriage processions (the night before the contract). This research is an empirical research that uses a legal anthropology approach with interviews as primary data and related literature as secondary data. This research uses a descriptive analysis method with 'urf (Islamic tradition theory) as the analysis tool. Finally, the results of this study show that the views of couples who marry using theGubang dance tradition fall into two categories: culture and belief. In the 'urf tradition, the Gubang dance tradition in the pre-marriage procession is included in al-'urf al-shahih.